Involvement of multiple CCN family members in platelets that support regeneration of joint tissues. Issue 6 (1st November 2016) - Hara, Chikako; Kubota, Satoshi; Nishida, Takashi; Hiasa, Miki; Hattori, Takako; Aoyama, Eriko; Moriyama, Yoshinori; Kamioka, Hiroshi; Takigawa, Masaharu
Abstract: Objectives : Platelet-rich plasma (PRP) has been widely used to enhance the regeneration of damaged joint tissues, such as osteoarthritic and rheumatoid arthritic cartilage. The aim of this study is to clarify the involvement of all of the CCN family proteins that are crucially associated with joint tissue regeneration. Methods : Cyr61-CTGF-NOV (CCN) family proteins in human platelets and megakaryocytic cells were comprehensively analyzed by Western blotting analysis. Production of CCN family proteins in megakaryocytes in vivo was confirmed by immunofluorescence analysis of mouse bone marrow cells. Effects of CCN family proteins found in platelets on chondrocytes were evaluated by using human chondrocytic HCS-2/8 cells. Results : Inclusion of CCN2, a mesenchymal tissue regenerator, was confirmed. Of note, CCN3, which counteracts CCN2, was newly found to be encapsulated in platelets. Interestingly, these two family members were not detectable in megakaryocytic cells, but their external origins were suggested. Furthermore, we found for the first time CCN5 and CCN1 that inhibits ADAMTS4 in both platelets and megakaryocytes. Finally, application of a CCN family cocktail mimicking platelets onto HCS-2/8 cells enhanced their chondrocytic phenotype. Conclusions : Multiple inclusion of CCN1, 2 and 3 in platelets was clarified, which supports the harmonized regenerative potential of PRP in joint therapeutics.